2007
DOI: 10.1109/fie.2007.4417807
|View full text |Cite
|
Sign up to set email alerts
|

Stressors faced by university students and their coping strategies: A case study of midlands state university students in Zimbabwe

Abstract: The study examined coping strategies used by students at a medium size developing country university. Participants constituted two hundred and eighty one Social Sciences students at the Midlands State University in Zimbabwe [49% female, 51% male]. A questionnaire was used to collect data. The results showed that the seven most common clusters of stressors were Finance, Library resources and study material, Accommodation, Food, Transport, Inadequate infrastructure and Lecturer related problems respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…There are also numerous external factors, such as congestion and unreliable public transport systems, which may result in some students arriving late, tired or missing lectures altogether with adverse effects on their learning. A study by Kasayira et al (2007) found that out of the 11 stressors that faced students at one university, transport ranked fifth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are also numerous external factors, such as congestion and unreliable public transport systems, which may result in some students arriving late, tired or missing lectures altogether with adverse effects on their learning. A study by Kasayira et al (2007) found that out of the 11 stressors that faced students at one university, transport ranked fifth.…”
Section: Literature Reviewmentioning
confidence: 99%